«Փափուկ ուժի» ռեսուրսները և իրացման ռազմավարությունը - Մինասյան, Նարեկ (YSU Journal of International Affairs, 2017)
The author presents the main resources of soft power in international relations - culture, political values and foreign policy, separately revealing each of them. Heemphasizes the importance of the difference between the potential and the real soft power, as well as the process of transformation of the potential soft power into the real one. The author outlines various strategies for the realization of the soft power of countries in international relations, taking into consideration the differences of the aims they pursue.
Keywords: Joseph Nye, soft power, soft power resources, attractiveness, image, strategy